2004
DOI: 10.1111/j.1440-1592.2004.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 and Interleukin-5 Reduce Crth2 Surface Expression on Human Eosinophils

Abstract: A BSTRACTBackground: Recently, a second prostaglandin D 2 (PGD 2 ) receptor, chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2), was identified. Because PGD 2 was reported to have chemotactic activity on eosinophils, CRTH2 expressed on eosinophils attracted interest as a receptor associated with eosinophil migration to, and accumulation at, inflammatory sites. To elucidate the mechanism regulating the expression of CRTH2 on eosinophils, the effects of PGD 2 , interleukin (IL)-4, IL-5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…We recently reported that CRTh2 levels were notably decreased on blood basophils and eosinophils from CSU subjects as compared to healthy controls [19]. This finding is consistent with ongoing in vivo receptor-ligand engagement, leading to CRTh2 receptor internalization [20, 21]. …”
Section: Introductionsupporting
confidence: 69%
“…We recently reported that CRTh2 levels were notably decreased on blood basophils and eosinophils from CSU subjects as compared to healthy controls [19]. This finding is consistent with ongoing in vivo receptor-ligand engagement, leading to CRTh2 receptor internalization [20, 21]. …”
Section: Introductionsupporting
confidence: 69%
“…philia. In contrast, IL-5 has been shown to desensitize eosinophils to PGD 2 by down-regulating the expression of CRTH2 (Hamada et al, 2004). Similar phenomenon has been observed in vivo; eosinophils isolated from IL-5 transgenic mice cannot bind to PGD 2 (Hirai et al, 2003).…”
Section: Discussionmentioning
confidence: 67%
“…Several reports have demonstrated the down-modulation upon activation [10,29,30,31]. CRTH2 expression on human Th 2 cells was reduced upon CD3/CD28 stimulation [29] and on human eosinophils upon either PGD 2 or IL-5 activation [30].…”
Section: Discussionmentioning
confidence: 99%